PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI OPERASI HITUNG PENJUMLAHAN DAN PENGURANGAN BERBANTUAN MEDIA KANTONG BILANGAN - Pitaloka, Diah; Al Wahid, Sucahyo Mas'an; Noer, Roby Zulkarnain (Mathematics Education And Application Journal (META), 2022)
Media or learning aids are reinforcement in stimulating interaction.between.teachers.and.students.so.that learning.activities can also be.effective.and.efficient. The type.of.research.used.is.classroom.action.research, namely research.conducted.by the teacher in.the.classroom.or at the.school.where.he.teaches.with.an.emphasis on improving or enhancing the learning process through 4 stages in the first cycle of planning, implementation, observation, and reflection. The research subjects were class I B students of SDN 029 Tarakan, totaling 28 students, and 17 boys. and 11 girls. The.results.of.the.study.were.the pre-cycle students' mathematics learning outcomes, namely 6 students with a percentage of 21.4% in the good category, 10 students with a percentage of 35.7% in the sufficient category, and 12 students with a percentage of 42.9% in the less category. Then the learning outcomes of the first cycle of meetings 1 and 2 there was an increase in the same 7 students with a percentage of 25% in the very good category, different at meeting 3 there was an increase in 9 students with a percentage of 32.1% in the very good category. in the good category, it was found that the learning outcomes of meetings 1 and 2 were 8 students with the same percentage of 28.6%, but decreased at meeting 3 as many as 6 students with a percentage of 21.4%, the rest of the students were still in the sufficient and less category. In cycle II, meetings 4,5 and 6 in the very good category experienced an increase of 1 student per meeting, in the good category there were 7 students at meetings 4 and 5, but increased by 1 student at meeting 6, in the sufficient category at meeting 4 there were 6 students, but experienced the same increase at meetings 5 and 6 amounted to 1 student, in the less category there was a decrease in the number of students, namely at meeting 4 there were 7 students, at meeting 5 there were 5 students and meeting 6 to 3 students. It can be concluded that the use of number pocket learning media can provide increased learning in addition and subtraction arithmetic operations material.Keywords: Addition and Subtraction, Improvement, Mathematics Learning Outcomes, Numbers Pocket Media Media atau alat bantu pembelajaran merupakan penguatan dalam merangsang interaksi.antara.guru dan siswa, sehingga.kegiatan.pembelajaran juga dapat menjadi efektif dan efisien.tujuan dari penelitian ini berupa hasil peningkatan belajar.matematika.materi.penjumlahan.dan.pengurangan.bilangan menggunakan alat.peraga kantong bilangan. Jenis.penelitian.yang.digunakan.adalah.penelitian.tindakan.kelas.(classroom action research).yaitu.penelitian.yang.dilakukan.oleh.guru.ke.kelas.atau.di.sekolah.tempat.mengajar.dengan.penekanan.pada.penyempurnaan.atau.peningatan.proses.pembelajaran.melalui.4.tahapan.dalam.I.siklus.perencanaan,.pelaksanaan,.pengamatan.dan.refleksi.Subjek.penelitian.siswa.kelas.I.B.SDN.029.Tarakan.yang.berjumlah.28.siswa,.17.laki-laki.dan.11.perempuan.Hasil.penelitian berupa nilai hasil belajar matematika siswa prasiklus yaitu terdapat 6 siswa dengan presentase 21,4 % kategori baik, 10 siswa dengan presentase 35,7 % kategori cukup, dan 12 siswa dengan presentase 42,9 % kategori kurang. Kemudian hasil belajar siklus I pertemuan 1 dan 2 terdapat peningkatan yang sama 7 siswa dengan presentase 25% kategori baik sekali, berbeda pada pertemuan 3 terdapat peningkatan 9 siswa dengan presentase 32,1 % kategori baik sekali. pada kategori baik, ditemukan hasil belajar pertemuan 1 dan 2 sebanyak 8 siswa dengan presentase yang sama 28,6%, namun mengalami penurunan pada pertemuan 3 sebanyak 6 siswa dengan presentase 21,4% selebihnya siswa masih dalam kategori cukup dan kurang. Pada siklus II pertemuan 4,5 dan 6 dalam kategori baik sekali mengalami peningkatan 1 siswa setiap pertemuannya, kategori baik terdapat 7 siswa pada pertemuan 4 dan 5, namun meningkat 1 siswa pada pertemuan 6, pada kategori cukup pertemuan 4 terdapat 6 siswa, tetapi mengalami peningkatan yang sama pada pertemuan 5 dan 6 sejumlah 1 siswa, pada kategori kurang mengalami penurunan jumlah siswa yaitu pada pertemuan 4 terdapat 7 siswa, pada pertemuan 5 terdapat 5 siswa dan pertemuan 6 menjadi 3 siswa. Dapat disimpulkan bahwa penggunaan media pembelajaran kanotng bilangan dapat memberikan peningkatan pembelajaran pada materi operasi hitung penjumlahan dan pengurangan.Â Kata kunci: Peningkatan, Hasil Belajar Matematika, Penjumlahan dan Pengurangan, Media Kantong Bilangan